STUDI KRITIS PROBLEMATIKA KURIKULUM PENDIDIKAN AGAMA ISLAM DI SEKOLAH - Mahmud; Fauziah Rusmala Dewi; Mukhlisin (Sekolah Tinggi Ilmu Ekonomi Darul Falah Mojokerto, 2023)
Problems with the Islamic Religious Education curriculum in schools,including: limited material, teacher qualifications, integration with thegeneral curriculum, 4) mismatch of material with current developments,measurement of student abilities, irrelevant PAI curriculum content, poorcurriculum implementation, lack of access to resources learning, limitedlearning time, and differences in views. One-roof education itself is aneducation system that integrates various levels of education, starting fromearly childhood education, basic education, secondary education, to higher education in one institution. Critical studies of one-stop education focus onseveral important aspects, including: Equality of access and opportunity,Community involvement, Inclusive and student-centered learning, Teacherprofessionalism development. Identification of PAI curriculum problemsolving solutions can be done through several methods: problemidentification, data collection, data analysis, involving stakeholders,determining solutions, implementing solutions, and evaluating solutions.Several solutions that can be implemented to solve PAI curriculum problemsinclude: increasing teacher competency through training and education,increasing the relevance of the curriculum to student needs, using teachingmethods that suit student needs, and using evaluation that is in line withlearning objectives.